Teaching innovation in economic history: Advances in the university teaching-learning process - Vázquez-Fariñas, María; Castro-Valdivia, Mariano (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The characteristics of current university teaching require a constant search for innovations that allow improvements to be introduced. This article aims to present the main methodologies and tools used during the 2021-2022 academic year to improve the teaching-learning process in the subject of Economic History in the Degree in Business Administration and Management at the University of Jaén. It has been found that the use of new alternative methodologies to the traditional ones has contributed to significantly improve the understanding of the contents, acquisition and evaluation of competences related to the subject, obtaining quite satisfactory results.